Effect of different light intensities on performance, welfare and behavior of turkey poults - Mohammed, Hesham; Ibrahim, Mohamed; Saleem, Al-Sadik (Journal of Advanced Veterinary and Animal Research, 2016)
Objective: Lighting requirements of birds have to be considered for choosing the optimal light intensity. Therefore, the experiment was carried out to study the effects of the different light intensities on performance, welfare and behavior of turkey poults. Materials and Methods: A total of 81 turkey poults aging 3 weeks were randomly selected and divided into three equal groups. The birds were subjected for 3 different light intensities (5, 25 and 50 lux) with 12 h photoperiod in 3 separate rooms. The growth performance parameters of the poults were measured; the parameters were body weight (BW), average feed intake (FI), average body weight gain (ABWG), relative growth rate (RGR), and feed conversion ratio (FCR). Besides, blood parameters and behavioral characters were observed. Results: Our results revealed that poults reared in low intensity (5 lux) had better performance (body weight gain, relative growth rate and feed intake). Also, final body weight was significantly higher in 5 lux. The cortisol level was lower in 5 lux than other 25 and 50 lux. Behavior of poults is affected by light intensities in our study, where feather preening, feather pecking and aggressive behaviors were significantly higher in birds housed in the highest intensity (50 lux). In the same way, drinking time was significantly higher in 25 lux. The poults tended to lay and rest on perches more under the lowest intensity (5 lux). Conclusion: It was concluded that, it is better to use moderate light intensity to improve previous parameters with avoiding abnormal behavior. http://dx.doi.org/10.5455/javar.2016.c126